1965
DOI: 10.1172/jci105292
|View full text |Cite
|
Sign up to set email alerts
|

Sterol and bile acid excretion in man and the effects of dietary fat.

Abstract: It is now well established that diets rich in saturated fatty acids lead to high levels of serum cholesterol, whereas diets rich in unsaturated fatty acids tend to be associated with lower levels. The mechanism by which these changes in serum cholesterol are induced by dietary fat is not known. One possible explanation for these effects would be either inhibition of cholesterol biosynthesis by unsaturated fats or stimulation of synthesis by saturated fats. The effects on synthesis, if any, could, in turn, be e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
1

Year Published

1968
1968
2008
2008

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(33 citation statements)
references
References 20 publications
3
29
1
Order By: Relevance
“…1 panied by an increased excretion of fecal endogenous neutral steroids as well as of exogenous neutral steroids if the diet contained cholesterol. However, as in several previous studies (12,27,28) in which no change in neutral steroid excretion was found during unsaturated fat feeding, in the present experiments no increase in fecal neutral steroids of endogenous origin was seen in 10 of 11 patients. Furthermore, in five patients in whom reliable measurements of absorption of exogenous cholesterol could be made, the substitution of unsaturated for saturated fat produced no significant decrease in the absorption of dietary cholesterol.…”
Section: Discussionsupporting
confidence: 86%
“…1 panied by an increased excretion of fecal endogenous neutral steroids as well as of exogenous neutral steroids if the diet contained cholesterol. However, as in several previous studies (12,27,28) in which no change in neutral steroid excretion was found during unsaturated fat feeding, in the present experiments no increase in fecal neutral steroids of endogenous origin was seen in 10 of 11 patients. Furthermore, in five patients in whom reliable measurements of absorption of exogenous cholesterol could be made, the substitution of unsaturated for saturated fat produced no significant decrease in the absorption of dietary cholesterol.…”
Section: Discussionsupporting
confidence: 86%
“…Sterol balance 17 provides a direct measure of endogenous biosynthesis rate expressed as the diff erence between fecal sterol excretion (cholesterol and bile sterols) and cholesterol intake. The necessary presumption is equilibrium of internal sterol pools which can take weeks or months to achieve.…”
Section: Methods For Determination Of Cholesterol Synthesis and Absormentioning
confidence: 99%
“…Others have found no significant differences in the turnover rate of biliary cholic acid (56,57), in the excretion of neutral steroids (58), or in the fecal excretion of bile acids and neutral sterols (59,60) in men given saturated or unsaturated fats in the diet. Spritz, Ahrens, and Grundy (60) suggested that, by exclusion, the hypocholesteremic effect of polyunsaturated fat is due to a redistribution of cholesterol from plasma into other body tissues.…”
Section: Introductionmentioning
confidence: 99%
“…The isotope balance method introduced by Hellman and associates in 1957 (42) is based upon two assumptions: first, that the 4-carbon atom of the cholesterol molecule is not metabolized to any significant extent in the body or in the intestinal lumen (73)(74)(75)(76)(77)(78) and, therefore, the metabolic products of cholesterol metabolism (bile acids and sterols) will contain the "4C label of the administered cholesterol-4-14C; and second, that the fecal end products of cholesterol metabolism have specific activities that closely parallel that of the serum cholesterol (42,50,59,(77)(78)(79)(80)(81)(82).…”
Section: Introductionmentioning
confidence: 99%